Gene expression associated with acute low thermal stress of Macrobrachium nipponense. (16th April 2021) - Wang, Long; Wang, Hui; Wu, Nan; Zhu, Chuankun; Wu, Xuejun; Ding, Chenlong; Li, Jiale
Abstract: In this study, the molecular mechanism of M .  nipponense to low temperature stress was studied by RNA‐Seq technology under the experimental conditions of low temperature stress group (5°C) and control group (25°C). The results showed that after 48 hours of low temperature stress, glycogen, as the direct energy source of M .  nipponense, was completely consumed, M .  nipponense upregulated the expression levels of G6PD and PK genes to catalyse the pentose phosphate pathway, and then, glucose was consumed as a rapid energy source to generate enough energy to meet the metabolic needs of the body. M .  nipponense upregulated the expression level of the desaturase gene (including: Acetyl‐CoA acetyl transferase, Fatty acid synthase, Delta‐9 desaturase), which catalysed the saturated fatty acids to unsaturated fatty acids, and restored of membrane fluidity. The oxidative stress caused by low temperature stress was coped with through significantly upregulating HSP family genes (mainly HSP60, HSP70 and HSP90). Under low temperature, M .  nipponense can inhibit the hydrolysis of protein by downregulating trypsin and arginase, so as to ensure enough protein as nutrients to carry out physiological activities. M .  nipponense upregulated the expression level of Serine proteinase, and then hydrolysed some proteins into free amino acids to synthesize haemocyanin, so as to improve the metabolic rate and capacity of carrying oxygen, to ensure survival. This study contributes to clarifying the mechanism of molecular response of M .  nipponense to low temperature stress, laying a foundation for further study on the molecular mechanism of cold tolerance of this commercially important species.